PENGARUH CITRA OBJEK WISATA UMBUL TLATAR BOYOLALI TERHADAP LOYALITAS PENGUNJUNG DENGAN KEPUASAN SEBAGAI VARIABEL MEDIASI - Lamidi - -; Marjam Desma Rahadhini (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2013)
ABSTRACT The objective of the research is to empirically analyses: (1) effect of destination image to tourist satisfaction, (2) effect of destination image to tourist loyalty, (3) effect tourist satisfaction to tourist loyalty, (4) effect of destination image to tourist loyalty, through tourist satisfaction as the mediating variable. Population on this research are all of Umbul Tlatar destination in Boyolali. The samples of this research consist of 100 tourist taken with purposive sampling. Data collecting with questionnaire technique through validity and reliability test. To test the hypothesis, the researcher uses the path analysis, meanwhile to process the data, the SPSS Release 12 program is used. The result reveals that (1) there is a significance effect between destination image to tourist satisfaction showed p value (0,000) < 0.05, thus supporting hypothesis 1; (2) there is no significance effect between destination image to tourist loyalty showed p value (0.206) > 0.05, thus not supporting hypothesis 2 ; (3) there is a significance effect between tourist satisfaction to tourist loyalty showed p (0.000) < 0.05, thus supporting hypothesis 3; (4) there is a significance direct effect of the destination image in Umbul Tlatar Boyolali to tourist loyalty, through tourist satisfaction as the mediating variable, showed coefficient of the indirect effect (0.385) is greater than that coefficient of the direct effect (0.125), thus supporting hypothesis 4. Keywords: destination image, tourist satisfaction, tourist loyalty.